Brief communication: A midtarsal (midfoot) break in the human foot. Issue 3 (17th May 2013) - DeSilva, Jeremy M.; Gill, Simone V.
ABSTRACT The absence of a midtarsal break has long been regarded as a derived feature of the human foot. Humans possess a rigid midfoot that acts as an efficient lever during the propulsive phase of bipedal gait. Non‐human primates, in contrast, have a more mobile midfoot that is adaptive for tree climbing. Here, we report plantar pressure and video evidence that a small percentage of modern humans (n = 32/398) possess both elevated lateral midfoot pressures and even exhibit midfoot dorsiflexion characteristic of a midtarsal break. Those humans with a midtarsal break had on average a significantly flatter foot than those without. Midtarsal breakers also had significantly more medial weight transfer (pronation) during the stance phase of gait than those without this midfoot mobility. These data are in accordance with Elftman (Clin Orthop 16 (1960) 41–45) who suggested that pronation aligns the axes of the transverse tarsal joint, permitting elevated midfoot mobility. Am J Phys Anthropol 151:495–499, 2013.© 2013 Wiley Periodicals, Inc.